The Variation in Imaging Method of Activation Detection Associated with Pain-Love-Empathy Brain Responses - Ahmad Ahyat, N.A.; Sazali, S.N.A.; Tamam, S. (Malaysian Association of Medical Physics (MAMP), 2024)
Vol 3 No 1 (page: 1-7)